Targeting staphylococcal enterotoxin B binding to CD28 as a new strategy for dampening superantigen-mediated intestinal epithelial barrier dysfunctions - Amormino, Carola; Russo, Emanuela; Tedeschi, Valentina; Fiorillo, Maria Teresa; Paiardini, Alessandro; Spallotta, Francesco; Rosanò, Laura; Tuosto, Loretta; Kunkl, Martina (Frontiers in Immunology, 2024)
Staphylococcus aureus is a gram-positive bacterium that may cause intestinal inflammation by secreting enterotoxins, which commonly cause food-poisoning and gastrointestinal injuries.Staphylococcal enterotoxin B (SEB) acts as a superantigen (SAg) by binding in a bivalent manner the T-cell receptor (TCR) and the costimulatory receptor CD28, thus stimulating T cells to produce large amounts of inflammatory cytokines, which may affect intestinal epithelial barrier integrity and functions. However, the role of T cell-mediated SEB inflammatory activity remains unknown. Here we show that inflammatory cytokines produced by T cells following SEB stimulation induce dysfunctions in Caco-2 intestinal epithelial cells by promoting actin cytoskeleton remodelling and epithelial cell-cell junction down-regulation. We also found that SEB-activated inflammatory T cells promote the up-regulation of epithelial-mesenchymal transition transcription factors (EMT-TFs) in a nuclear factor-kB (NF-kB)-and STAT3-dependent manner. Finally, by using a structure-based design approach, we identified a SEB mimetic peptide (pSEB116-132) that, by blocking the binding of SEB to CD28, dampens inflammatory-mediated dysregulation of intestinal epithelial barrier.